GAMBARAN HISTOPATOLOGI KULIT MENCIT PUTIH (Mus musculus) SETELAH DIBERI PAPARAN ASAP PEMBAKARAN - Maria Aditya Pardomuan H; Wiwit Ade Widiawati; Alida Fidiawaty (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2017)
ABSTRACTForest fire commonly becomes a problem throughout the world. Its smoke contains a greatamount of gas like carbon monoxide (CO), nitrogen dioxide (NO2), particulate matter (PM),and volatile organic compounds (VOCs) which consist of formaldehyde, benzene, andacrolein released to the atmosphere, sulfur dioxide (SO2), and Ozone (O2). The smoke canalso cause skin disorder. The object of this research was to find out the influence of thesmoke of organic burning on the histophatological description in the skin of mice (Musmusculus) within 7 days and 14 days. The research used 18 white male mice that were 2-3days with the duration of 10 minutes/day. Control (C) was not given the smoke exposure. Theperiod of smoke exposure in the treatment 1 (T1) was 7 days and in the treatment 2 (T2) was14 days. The changes in the skin thickening and the accumulation of inflammation cells wereassessed by using a microscope. The result of the research showed that C = 8.3 μm; T1 =13.8 μm; T2 = 16.8 μm and there was no accumulation of inflammation cell infiltration in thecontrol, while there was the accumulation of inflammation cell infiltration in T1 and in T2.The conclusion of the research was that there were the changes in histophatologicaldescription in the skin of white mice (Mus musculus) after they were exposed with smoke.Keywords: Accumulation of Inflammation Cells, Forest Fire, Mice’s Skin Thickening